Pulmonary Infection by Blastoschizomyces capitatus in An old Tuberculosis Patient - Chauhan, Sapna (J Clin Diagn Res, 2015)
Blastoschizomyces capitatus is an arthrospore filamentous fungus. Lung infection by Blastoschizomyces can develop as an opportunistic infection in patients with underlying conditions especially when there is immunosuppression including neutropenia. However, it can occur in non-neutropenic patients with solid organ transplant and patients whose local pulmonary defenses are altered by chronic underlying lung pathology. We report here a case of pulmonary infection by B. capitatus in an old tuberculosis patient.